Portfolio Construction: A Case Study on High Market Capitalization Stocks in Bangladesh (Global Journal of Management and Business Research, 2018)
Diversified investment of capital reduces the unsystematic risk for an investor Desired maximization of return and minimization of risk can be achieved by assigning available capital into different assets in certain weights This paper constructs that optimal portfolio for an investor using stocks of 12 companies which represent 8 different industries selected from DS30 index After adjusting 2012-2017 monthly price data for right share stock dividend stock split and cash dividend monthly returns are used to calculate the excess return per unit of risk of the constructed portfolio In the equal weight case of all the 12 stocks the annual excess return is 4 35 with a standard deviation of 0 22 leading to a Sharpe Ratio of 19 49 The extent of diversification is demonstrated by optimizing the portfolio to maximize theta In the optimal portfolio case the excess return increases to 19 37 whereas the volatility decreases to 0 20 and this increased the Sharpe Ratio to 98 88 The stocks included in the optimized portfolio are BRAC Bank Ltd IFAD Autos Ltd Olympic Industries Ltd MJL Bangladesh Ltd Beximco Pharmaceuticals Ltd and Grameenphone Ltd The impact of diversification is further established by constructing the global minimum variance portfolio
Keywords: sharpe ratio; optimal portfolio; excess return; volatility